Why educators endorse a neuromyth: relationships among educational priorities, beliefs about learning styles, and instructional decisions - Bresnahan, Christine; Peterson, Emily Grossnickle; Hattan, Courtney (Frontiers in Psychology, 2024)
Despite evidence to the contrary, many people believe in learning styles (LS)-the idea that students learn best in their preferred modality, such as visual, auditory, or kinesthetic.However, the impact of this belief on instructional decisions remains unclear. Therefore, this study investigated how belief in the neuromyth impacts instructional choices and why educators choose an LS lesson plan or an alternative. We found that educators' beliefs about LS indeed predicted their instructional choice, but that other factors influenced their decisions as well. Three themes encapsulate educators' justifications for their lesson plan choices: beliefs about LS, practical considerations, and student learning and motivation.These findings suggest that for many educators, implementing an LS lesson provides an opportunity to integrate diverse teaching strategies that address multiple educational priorities. Although many prior studies have replicated the prevalence of the myth, this is one of the first to explore the reasons that LS is attractive to educators. Attempts to dispel the LS neuromyth could leverage the reasons educators find LS appealing to provide alternative research-backed approaches to meet their goals. Future research should examine the extent to which beliefs in the LS neuromyth are translated into instructional practices within classroom lessons and explore potential differences across grade levels.